Exchange rate dynamics in a target zone: a heterogeneous expectations approach - Christian Bauer; Paul De Grauwe; Stefan Reitz (Deutsche Bundesbank, 2007)
We present a simple behavioral model with chartists and fundamentalists and analyze their trading behavior in a floating regime and in a target zone regime. Regarding the floating regime the model replicates the well-known stylized facts like excessive volatility, fat tails, volatility clustering and the exchange rate disconnect. When introducing a credible target zone the exchange rate remains for a considerably long period in the center of the band albeit the fundamental exchange rate does not exhibit mean reversion tendencies. The resulting hump-shaped distribution of the exchange rate greatly reduces the frequency of central bank intervention. The introduction of a target zone regime significantly reduces exchange rate volatility by decreasing speculative activity in the FX market.
Keywords: F31; F41; 330; Exchange rate; heterogeneous agents; target zones; Wechselkurs; Target Zone; Wertpapierhandel; Anlageverhalten; Agent-based Model; Theorie